Decision analysis of shifting lng business model from upstream to downstream in pt badak ngl using analytic hierarchy process (ahp) - Gugun Gumati, Anggun; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2016)
Abstract â€” PT Badak NGL is one of vital asset that Indonesia has. Currently, PT Badak NGL is Non-profit Entity that has been operated by join management group (JMG). All of operational expenditure will be claimed to the gas producers without take any profit for the company. Government, based on law 22/2001, actually has another option of business model that is possible to be applied in this company. The option is downstream business model. Downstream model allows LNG Company like PT Badak NGL to take margin from selling gas. For making decision shifting from existing business model to new business model, there are two big questions; comparing two business model which business model is considered give higher value of business? And what factors should be considered to make that decision? The selection process of those business models can be considered as multi-criteria decision making problem, and AHP (Analytic Hierarchy Process) is one of the tools available that can be used to answer those two questions. Before answering the question which business model is better than the other, it needs to define decision criteria or sub criteria. It would answer second question regarding factor that should be considered for making decision. And at the end it would to compare both business models with considering that factors or criteria to answer which business model that give higher value of business. There are 4 main factors that should be considered. Those are company growth, supply growth, government control and buyer. The decision maker is MoEMR. In this research, the recommendation for the decision makers comes from SKK Migas and PT Badak NGL. SKK Migas consider that upstream model has higher value of business and the most valuable factor is government control (51%). Company growth (5.6%) is the last one. In the other side, PT Badak NGL consider downstream has higher value of business and most valuable factor is company growth (64.1%). All of that individual judgment is merged in group decision. The most important factor is government control (41.9%). The second one is supply growth (30%). The third one is company growth (15.5%) and the last one is Level of LNG Delivery Guarantee for buyer (11.7%). Based on AHP Calculation the upstream (55.5%) model is considered having higher value of business compared to downstream (44.5%). This final project recommends that PT Badak NGL still use upstream model. But, there are significant gap between government perspective and internal company perspective about company growth. Even PT Badak NGL still use existing business model, government should be more involved to improve growth of PT Badak NGL.Â Keywords: AHP, LNG, Indonesia LNG, Business Model, Upstream, DownstreamÂ